Three-Dimensional Conformal Radiotherapy for Hepatocellular Carcinoma in Patients Unfit for Resection, Ablation, or Chemotherapy: A Retrospective Study - Vassilis Kouloulias; Eftychia Mosa; John Georgakopoulos; Kalliopi Platoni; Ilias Brountzos; Anna Zygogianni; Christos Antypas; Paraskevas Kosmidis; Kyriaki Mystakidou; Maria Tolia; Ivelina Beli; Athanasios Gouliamos; et al. (The Scientific World Journal)
Purpose. The purpose is to evaluate the feasibility, efficacy, and the toxicity of three-dimensional conformal radiotherapy (3DCRT) in patients with advanced hepatocelluar carcinoma (HCC) and inferior vena cava tumor thrombosis (IVCTT). Methods. Between 2007 and 2012, in a retrospective way, 9 patients (median age 69 years) with advanced HCC and IVCTT unfit for surgery, radiofrequency ablation, embolization, or chemotherapy were treated with three-dimensional conformal radiotherapy (3DCRT). The radiotherapy volume included both primary tumor and IVTT. The radiotherapy schedule was 50–52 Gy in 2 Gy fractions. Overall survival (OS), response to radiotherapy, visual analogue scale (VAS), and toxicity were assessed. Results. All patients demonstrated a response rate up to 60%. During radiotherapy, 3 patients experienced grade 1 nausea/vomit toxicity. All patients demonstrated an elevation of the liver enzymes (3 patients with grade 1 and 6 patients with grade 2). The mean VAS-score was decreased from 6.11 to 3.11, while the median overall survival was 24 months. Conclusion. 3DCRT achieves a very high local control rate and is suitable for patients with HCC and IVTT, while the documented radiation induced toxicity is moderate. It can be recommended for palliation in patients unable to undergo curative therapies.